Transforming Private Islamic Religious Colleges (STAIS) into Institutes (IAIS) to Enhance the Quality of Private Islamic Religious Higher Education (PTKIS) - Yusraini, Yusraini; Maisah, Maisah; Musli, Musli (Yayasan Sembilan Pemuda Indonesia, 2024)
The purpose of this study is to describe the factors driving the transformation, the process of converting Private Islamic High Schools into Private Islamic Religious Institutes in Jambi Province, and to assess the quality of education in Private Islamic High Schools before and after the transformation. The researcher conducted field research using qualitative research methods and a phenomenological approach. Data was collected through observation, interviews, and documentation. Data analysis includes data reduction, presentation, verification, and conclusion. This research produces results: first, the factors that influenced the transformation of Islamic Religious Colleges in Jambi Province into Islamic Religious Institutes can be divided into two categories: internal and external factors. Second, implementing the transformation into Islamic Religious Institutes through the history of IAI, specifically Bungo and Nusantara Batanghari, the pioneering period, the STAIS periods, and the IAIS periods. Third, the quality of education before transformation, namely the lack of socialization of vision, mission, and goals to external parties. Fourth, the quality of PTKIS education after transformation, namely developing campus resources and involving lecturers to continue to doctoral and master’s programs for employees at universities, etc.